2020
DOI: 10.3892/ijmm.2020.4675
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‑145 promotes the apoptosis of leukemic�stem�cells and enhances drug‑resistant K562/ADM cell�sensitivity to adriamycin via the regulation of ABCE1

Abstract: Leukemia is a type of cancer which originates in blood-forming tissues. MicroRNAs (miRNAs or miRs) have been shown to be involved leukemogenesis. In the present study, following the gain- and loss-function of miR-145 and ATP-binding cassette sub-family E member 1 (ABCE1) in K562 cells and K562 adriamycin-resistant cells (K562/ADM cells), the levels of multidrug resistance protein 1 (MRP1) and P-glycoprotein (P-gp) were measured. The viability of the K562 cells and K562/ADM cells treated with various concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…MicroRNAs (miRNAs) are small,endogenous,non-coding RNA molecules that play pivotal roles in numerous biological processes including developmental timing, cell differentiation, embryogenesis, metabolism, organogenesis, apoptosis, and tumorigenesis [3,4] . Research has demonstrated that miRNA downregulation is prevalent in various cancers and is linked to cancer development,metastasis,and treatment response [5] . a relatively new discovery in the miRNA category,has been identi ed in WT through clinical data and specimen analysis.Increasing miR-145 levels have been shown to suppress the proliferation and migration of WT SK-NEP-1 cells, suggesting its role as a tumor suppressor gene [6] .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small,endogenous,non-coding RNA molecules that play pivotal roles in numerous biological processes including developmental timing, cell differentiation, embryogenesis, metabolism, organogenesis, apoptosis, and tumorigenesis [3,4] . Research has demonstrated that miRNA downregulation is prevalent in various cancers and is linked to cancer development,metastasis,and treatment response [5] . a relatively new discovery in the miRNA category,has been identi ed in WT through clinical data and specimen analysis.Increasing miR-145 levels have been shown to suppress the proliferation and migration of WT SK-NEP-1 cells, suggesting its role as a tumor suppressor gene [6] .…”
Section: Introductionmentioning
confidence: 99%
“…Wu at al. (2021) described that both IL-6 and IL-8 levels are increased in resistant acute myeloid leukemia cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, IL-8 could promote proliferation and resistance in acute myeloid leukemia cells, while IL-6 predicts survival rate and regulates the drug resistance in these cells [57].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Let-7, miR-23A, and miR-223 have been reported to act as tumor suppressors in CML ( 29 31 ). miR-145 and miR-181 promote apoptosis of leukemia stem cells through regulation of ABCE1 and MCL-1 respectively ( 32 , 33 ), and miR-424 inhibits BCR-ABL activity ( 34 ). Comparatively, the miR-126 is associated with leukemia stem cell maintenance ( 35 ), miR-17 promotes leukemia proliferation by targeting p21 ( 36 ), over-expression of miR-106 and miR-222 will promote CML proliferation ( 37 ), and miR-92a-1-5p inhibits TKI-induced necroptosis by targeting MLKL ( 38 ).…”
Section: Discussionmentioning
confidence: 99%